Prinsip-Prinsip Metodologis dan Organisasi Gramatika Fungsional - Muh. Yazid Abdul Rahim Gege (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2014)
Due to Van Valin (2001: 329), there are three theories of currently linguistics functional, (a) Functional Grammar that influenced by Simon Dik, (b) Systemic Functional Grammar that influenced by M.A.K Halliday, and (c) Role and Reference Grammar that influenced by William Foley, Robert D. Van Valin, Jr. and Randi J. LaPolla. In this article aimed to explain the Functional Grammar used in communication, its approaches, the principles of methodologies, and the organization of functional grammar. Key words: functional grammar, principles of methodologies, organization of functional grammar.